Can the solvent enhance the rate of chemical reactions through C-H/pi interactions? insights from theory - Jain, Shailja; Vanka, Kumar (Physical Chemistry Chemical Physics, 2019)
The current computational study with density functional theory (DFT) shows that the rate of chemical reactions can be influenced through non-covalent C-H/p interactions between substrates and the solvent. It is shown that intramolecular carbon-carbon interaction and CO2 activation by a low valent silicon complex are both favourably affected by the explicit presence of the solvent toluene, due to C-H/p interactions between toluene and the silicon complex. Furthermore, ab initio molecular dynamics (AIMD) simulations demonstrate that even if the C-H/p interacting solvent molecule is displaced from the complex, another would quickly take its place, thus maintaining the interaction. Hence, the current work shows how non-covalent interactions between solvent and substrate can enhance the rate of the reaction and expands our understanding of the role and influence of the solvent in effecting important chemical transformations.